The Ile585Val TRPV1 variant is involved in risk of painful knee osteoarthritis. Issue 9 (25th May 2011) - Valdes, Ana M; De Wilde, Gert; Doherty, Sally A; Lories, Rik J; Vaughn, Frances L; Laslett, Laura L; Maciewicz, Rose A; Soni, Anushka; Hart, Deborah J; Zhang, Weiya; Muir, Kenneth R; Dennison, Elaine M; et al.
Abstract : Objective: To assess if a coding variant in the gene encoding transient receptor potential cation channel, subfamily V, member 1 ( TRPV1 ) is associated with genetic risk of painful knee osteoarthritis (OA). Methods: The Ile585Val TRPV1 variant encoded by rs8065080 was genotyped in 3270 cases of symptomatic knee OA, 1098 cases of asymptomatic knee OA and 3852 controls from seven cohorts from the UK, the USA and Australia. The genetic association between the low-pain genotype Ile–Ile and risk of symptomatic and asymptomatic knee OA was assessed. Results: The TRPV1 585 Ile–Ile genotype, reported to be associated with lower thermal pain sensitivity, was associated with a lower risk of symptomatic knee OA in a comparison of symptomatic cases with healthy controls, with an odds ratio (OR) of 0.75 (95% CI 0.64 to 0.88; p=0.00039 by meta-analysis) after adjustment for age, sex and body mass index. No difference was seen between asymptomatic OA cases and controls (OR=1.02, 95% CI 0.82 to 1.27 p=0.86) but the Ile–Ile genotype was associated with lower risk of symptomatic versus asymptomatic knee OA adjusting for covariates and radiographic severity (OR=0.73, 95% CI 0.57 to 0.94 p=0.0136). TRPV1 expression in articular cartilage was increased by inflammatory cytokines (tumour necrosis factor α and interleukin 1). However, there were no differences in TRPV1 expression in healthy and arthritic synovial tissue. Conclusions: A genotype involved in lower peripheral pain sensitivity is significantly associated with a decreased risk of painful knee OA. This indicates a role for the pro-nociceptive gene TRPV1 in genetic susceptibility to symptomatic knee OA, which may also be influenced by a role for this molecule in cartilage function.